Integrasi GeoGebra Dalam Pembelajaran Matematika Terhadap Pemahaman Konsep Matematis Siswa - Cahyani, Nurriza Indah; Kurniawan, Eka; Arjudin; Kurniati, Nani (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study was motivated by the low level of students' understanding of mathematical concepts, which is partly due to the limited use of innovative learning media. The purpose of this research is to determine the effect of GeoGebra integration on students' conceptual understanding of three-dimensional geometry in grade XI at SMAN 1 Pringgasela in the 2024/2025 academic year. This research employed a mixed-methods approach with a concurrent embedded design, emphasizing the quantitative aspect. The sample consisted of two classes: the experimental class, which used the Problem-Based Learning model assisted by GeoGebra, and the control class, which used conventional learning. The posttest results showed that the average score of the experimental class was 82.71, while the control class scored 53.94. The t-test showed a significance value (2-tailed) of 0.000, which is ≤ 0.05, indicating a significant difference between the two groups. Furthermore, the effect size value of 2.32 falls into the large category, indicating that GeoGebra integration had a significant impact on improving students’ conceptual understanding. Thus, the use of GeoGebra has proven effective in enhancing the quality of mathematics learning, particularly in three-dimensional geometry topics.